Filogenia molecular dos anostomidae e filogeografia das espécies com cromossomos sexuais ZZ/ZW do gênero Leporinus - Malaver, Jorge Luis Ramirez (Universidade Federal de São Carlos, 2015)
The family Anostomidae has approximately 150 species, belonging to 14 genera. Several attempts to define the subfamilies were unsuccessful. Within the family, the Leporinus genus is the most specious (approx. 90 valid species). A ZZ/ZW sex chromosomes system has been described for seven species of Leporinus, which would constitute a monophyletic group. Another ZW sex chromosomes system has been described only for Leporinus geminis. The ZW Leporinus species presents an interesting distribution, being distributed in almost every major South American basins. The aim of this study was to reconstruct the phylogenetic relationships of family Anostomidae and several species of Leporinus genus. Also, evaluate the monophyly of species with ZZ/ZW sex chromosomes, as well as de novo origin of the sex chromosomes described for Leporinus geminis. Additionally, It will be evaluated the functionality of the DNA barcodes for the family Anostomidae. Another aim was to evaluate the phylogeographic distribution pattern of ZZ/ZW Leporinus species. For the barcode was analyzed the Cytochrome Oxidase subunit I of 430 individuals (122 lineages). Distance analyzes were performed using the K2P model. For the molecular phylogeny were amplified two mitochondrial genes (Cytochrome B and Cytochrome Oxidase I) and three nuclear markers (recombination activating gene 1 and 2, and Myosin, heavy chain 6, cardiac muscle, alpha gene) from 104 lineages (69 nominal species). Phylogenetic trees were constructed using methods of maximum parsimony, maximum likelihood and Bayesian species tree. For the phylogeographic analysis, was constructed a calibrated tree, including the 15 recovered linages for the ZW group. The dataset was calibrated using the rise of the Eastern Cordillera, about 12 million years ago. The DNA barcode is a powerful tool for the linage identification of the family Anostomidae. The average intraspecific distance was 0.106%. The lowest interspecific distance was 0.479%. The genetic distances founded show that the threshold to separate lineages is lower than traditionally suggested for fishes (1% and 2%). The family Anostomidae is monophyletic, being found twenty-two clades within it. The subfamilies Anostominae sensu Winterbottom (1980) and Leporellinae were recovered as valid, while a more inclusive Leporininae has to be redescribed. The Leporinus genus was recovered as paraphyletic, requiring several taxonomic changes. The ZZ/ZW Leporinus species were recovered as a monophyletic group. Sex chromosomes of Leporinus geminis were confirmed as an evolutionary convergence. The evolutionary history of ZZ/ZW Leporinus species proved to be complex. The lineage speciation of the proto-Amazon-Orinoco was given by paleogeographic processes, while the lineage diversification in the Eastern Brazilian Shield was predominantly hydrogeological and by dispersion through paleo-basins in low sea level period.
Keywords: Filogenia molecular; Anostomidae; Leporinus; DNA Barcode; Filogeografia; Molecular phylogeny; Anostomidae; DNA Barcode; Leporinus; Phylogeography; OUTROS